Infection Control Practice on Vital Signs Equipment: A Survey Among Senior Nursing Students in Iloilo City, Philippines - Zea Maize S. Suarez; Ryan Michael F. Oducado; Eric Lorenz C. Josue; Treesha Llen C. Gayoso; Christy Anne L. Ocate; Janelene Joy A. Lujan (Asia Pacific Journal of Multidisciplinary Research, 2019)
Blood pressure apparatuses, stethoscopes and thermometers serve as vehicles for pathogens. Previous studies have shown that these equipment harbor potentially pathogenic microorganisms and even antibiotic-resistant strains within the hospital environment. Practice of good infection control on vital signs equipment therefore plays an important role in preventing the spread of infections that can be acquired during hospitalization. However, studies on infection control practice on these equipment among nursing students have not been given much attention. This descriptive cross-sectional study was conducted to determine the senior nursing students' practice of infection control on vital signs equipment. A researchermade, self-administered survey instrument was used to collect data among 202 randomly selected senior nursing students in six nursing schools in Iloilo City, Philippines. Descriptive and parametric inferential statistical tools were employed to analyze and interpret the data gathered. Results indicated that while a higher proportion of nursing students almost always disinfected their thermometers, only one out of five almost always disinfected their BP apparatuses, and only two out of five almost always performed disinfection of their stethoscopes after each patient use and every after clinical duty. Forgetfulness and laziness in doing the disinfection process were the primary reasons for non-disinfection. A significant correlation was found between nursing students' self-report infection control practice and the infection control practice of their fellow nursing students. It is evident that there are senior nursing students that do not regularly practice high standard infection control of their vital sign's equipment. Strengthening practice, modeling good behaviors, and adopting clear guidelines on infection control of vital signs equipment must be initiated in the undergraduate nursing program.
Keywords: 330; infection control; disinfection; vital signs; role modeling; social learning; nursing students